KRAS and BRAF Mutation Detection: Is Immunohistochemistry a Possible Alternative to Molecular Biology in Colorectal Cancer? - Nicolas Piton; Francesco Borrini; Antonio Bolognese; Aude Lamy; Jean-Christophe Sabourin (Gastroenterology Research and Practice)
KRAS genotyping is mandatory in metastatic colorectal cancer treatment prior to undertaking antiepidermal growth factor receptor (EGFR) monoclonal antibody therapy. BRAF V600E mutation is often present in colorectal carcinoma with CpG island methylator phenotype and microsatellite instability. Currently, KRAS and BRAF evaluation is based on molecular biology techniques such as SNaPshot or Sanger sequencing. As molecular testing is performed on formalin-fixed paraffin-embedded (FFPE) samples, immunodetection would appear to be an attractive alternative for detecting mutations. Thus, our objective was to assess the validity of KRAS and BRAF immunodetection of mutations compared with the genotyping reference method in colorectal adenocarcinoma. KRAS and BRAF genotyping was assessed by SNaPshot. A rabbit anti-human KRAS polyclonal antibody was tested on 33 FFPE colorectal tumor samples with known KRAS status. Additionally, a mouse anti-human BRAF monoclonal antibody was tested on 30 FFPE tumor samples with known BRAF status. KRAS immunostaining demonstrated both poor sensitivity (27%) and specificity (64%) in detecting KRAS mutation. Conversely, BRAF immunohistochemistry showed perfect sensitivity (100%) and specificity (100%) in detecting V600E mutation. Although molecular biology remains the reference method for detecting KRAS mutation, immunohistochemistry could be an attractive method for detecting BRAF V600E mutation in colorectal cancer.